The Contribution of Mohammad Natsir's Thoughts in The Formation of The Unitary State of The Republic of Indonesia (NKRI) Perspective of Religious Moderation Da'wah - Ali Abdurrahim (Jurnal Syntax Transformation, 2023)
This research is qualitative in nature which produces descriptive data. This research is a type of library research, which is conducting research by studying and reading literature that has to do with the problem that is the object of research. This type of research is included in the explanatory, which is looking for new things from historical facts in the form of the application of Mohammad Natsir's da'wah thought to then be formulated analytically as a strategy pattern in religious moderation da'wah using descriptive analysis methods. This technique begins with reducing data, then organizing and explaining, verifying then ending with impending data on "The Contribution of Mohammad Natsir's Thought in the Formation of the Sovereign State of the Republic of Indonesia (NKRI) Perspective of Da'wah Religious Moderation". The purpose of this study is to find the concept of Religious Moderation Da'wah Mohammad Natsir and its implementation in the formation of the Republic of Indonesia. The concept of Da'wah Religious Moderation carried out by Mohammad Natsir by explaining what Mohammad Natsir's contribution to the Republic of Indonesia and in preaching, The concept of Mohammad Natsir's religious moderation da'wah is Robbaniyah, Tawasut and Tasammuh, then implemented in: First in Statehood this is illustrated during the discussion of Pancasila, Islam as the basis of the state, Integral Motion and tolerance towards political opponents. Second, in Da'wah by conducting inter-religious dialogue, proposing Modus Vivendi, socializing the Islamic Concept, da'wah against Sekularism and establishing a Da'wah Institute (Dewan Dakwah Islamiyah Indonesia / DDII). Third in Education by establishing educational institutions such as UII, UIKA, Bandung Islamic University, Islamic University of North Sumatra, Riau University, STID and Pendis. Mohammad Natsir also initiated the Concept of Integral Education by uniting Campuses, Mosques and Pesantren.